PTH-289 The poor overall survival of right-sided colon cancer compared with left-sided colon cancers: a systematic review and meta-analysis. (22nd June 2015) - Yahagi, M; Okabayashi, K; Hasegawa, H; Tsuruta, M; Kondo, T; Shimada, T; Matsuda, M; Yoshikawa, Y; Asada, Y; Sugiura, K; Suzuki, Y; Tajima, Y; et al.
Abstract : Introduction: Right-sided colon cancers (RCC) and left-sided colon cancers (LCC) are of different embryological origins, and there are various differences between them. However, the survival difference has not been evaluated. The aim of the present study was to quantify the difference of prognosis between RCC and LCC by meta-analysis. Method: PubMed and the Cochrane Library were searched during May 2014 for literature on right- versus left-sided colon cancers. The MeSH terms "colonic neoplasm" and the terms "prognosis" or "survival analysis" were combined with terms "left" and "right" or "sub site". The effects of tumour locations on survival outcome (overall survival [OS] and cancer-specific survival [CSS]) were assessed. Hazard ratio (HR) was used as a surrogate for effect size, and random-effects meta-regression was applied as a method to evaluate the influences of covariates. Heterogeneity and publication bias were assessed. Results: 15 studies (108, 474 participants) which compared the prognosis of colon cancer according to tumour location were included. With respect to OS, patients with RCC had a significantly worse prognosis (HR = 1.14, 95% conﬁdence interval [CI]: 1.06 –1.22, p < 0.01, I 2 = 41.82%) than those with LCC. Though, this tendency was not evident for CSS, which might be because CSS was evaluated by a small number of studies included in this analysis. Subgroup analyses demonstrated significant prognostic differences in Western countries (HR = 1.15, 95% CI: 1.08 – 1.23, p < 0.01), a nationwide database (HR = 1.15, 95% CI: 1.05 – 1.27, p = 0.01), and a stage-adjusted analysis (HR = 1.14, 95% CI: 1.05 – 1.24, p < 0.01). The test of funnel plot identified no publication bias. The source of heterogeneity was not identified in meta-regression. Conclusion: Our findings indicate that tumour location is closely associated with prognosis in colorectal cancer patients, and those with RCC have a significantly worse prognosis than those with LCC in regards to OS. Therefore, RCC should be treated distinctively from LCC, and the establishment of standardised management for colon cancer by tumour location is needed. Disclosure of interest: None Declared.